Desmame em recém-nascidos de muito baixo peso ao nascer no primeiro retorno ambulatorial após a alta hospitalar - Maia, Cláudia Rodrigues Souza (2010)
Investigate intrahospital and neonatal determinants associated to the weaning of very low birth weight (VLBW) infants. Methods: 119 VLBW (<1500g) infants 81 were monitored from July 2005 through August 2006, from birth to the first ambulatory visit after maternity discharge. This maternity unit uses the Kangaroo Method and the Baby Friendly Hospital Initiative. Results: Out of 119 VLBW infants monitored until discharge, 88 (75%) returned to the facility, 22 (25%) were on exclusive breastfeeding (EB) and 66 (75%) were weaned (partial breastfeeding or formula feeding). Univariate analysis found an association between weaning and lower birth weight, longer stays in the NICU and longer hospitalization times, in addition to more prolonged enteral feeding and birth weight recovery period. Logistic regression showed length of NICU stay as being the main determinant of weaning. Conclusion: The negative repercussion on EB of an extended stay in the NICU is a significant challenge for health professionals to provide more adequate nutrition to VLBW infants